A study to assess the feasibility of using CT (±diagnostic MRI) instead of MRI at brachytherapy in image guided brachytherapy in cervical cancer. Issue 4 (13th February 2014) - Rai, Bhavana; Patel, Firuza D.; Tomar, Parsee; Singh, Oinam A.; Simha, Vijai; Dhanireddy, Bhaswanth; Sharma, Suresh C.
Abstract Purpose To compare the contours and dose volume histograms (DVH) parameters of the high-risk clinical target volume (HRCTV) contoured on computed tomography (CT) using clinical findings at brachytherapy, clinical findings at brachytherapy with magnetic resonance imaging (MRI) at diagnosis and HRCTV defined on MRI at brachytherapy in cervical cancer patients. Materials and methods Fifteen patients undergoing MRI-guided image-based brachytherapy underwent both CT and MRI after applicator insertion. Two sets of contours were defined on CT. In the first set, the HRCTV was defined with the help of clinical findings at brachytherapy (CT-HRCTV). In the second set, HRCTV was defined with MRI at diagnosis and clinical findings at brachytherapy (CT-HRCTVdmri). This was compared with the HRCTV defined on MRI at brachytherapy (MR-HRCTV). The doses to the organs at risk (OARs) were compared for CT and MRI. Results A significant overestimation of the maximum width and width at point A was observed for CT-HRCTV (p −0·00; 0·00) and CT-HRCTVdmri (p −0·03; 0·01), respectively. The height was underestimated with CT-HRCTV in patients with intrauterine disease extension. For a single fraction, the mean difference in the D90 for the CT contours was <1 Gy. The doses to the OARs were comparable. Conclusions CT may be an alternative when facilities for MRI image-based brachytherapy are lacking, provided at least one MRI is available before brachytherapy.